Meningkatkan Kesadaran Bertanggung Jawab Sebagai Remaja Pada Siswa Kelas VIII UPT SMP Negeri 10 Medan Melalui Layanan Bimbingan Kelompok - Prameswari, Sekar Aulia; Syaimi, Khairina Ulfa; Husna, M. Faisal; Febrianti, Aliyah (CV. PUSDIKRA MITRA JAYA, 2025)
Currently, there are so many students who do not have the awareness to be responsible according to their age. This often happens to students who are teenagers. The low awareness of responsibility in students certainly greatly interferes with the effectiveness of their lives so that appropriate efforts are needed in this case, namely group guidance. The purpose of this study was to describe the increase in awareness of responsibility as teenagers in class VIII students of SMP Negeri 10 Medan. The research method used was guidance and counseling action research (PTBK) which was carried out through 2 cycles. The research subjects used were 8 students selected using purposive sampling techniques. The results of this study were that in the pre-cycle, students were at a low awareness of responsibility with an average score of 38.6. In cycle I, there was an increase so that students' awareness of responsibility was in the low category with an average score of 61.25. After cycle II was implemented, students experienced a significant increase in awareness with an average score of 84.75. Thus, group guidance services are stated to be able to increase awareness of responsibility as teenagers in students.